ULTRASOUND DIAGNOSIS OF HIP DYSPLASIA IN INFANTS - Shirov Bobur Furkatovich (Scholar Express Journals, 2022)
In the structure of all congenital malformations of the musculoskeletal system, hip dysplasia occurs most frequently. Until recently, the main method for diagnosing pathology of the hip joint was radiological, recording changes only in the bone structures, the number of which in children in the first months of life is relatively small. According to various authors, an x–ray examination of the hip joints becomes informative at the age of no earlier than 3–5 months of life. In our work, ultrasonographic diagnostics of hip joint dysplasia in infants is presented, which made it possible to identify this pathology at the earliest stages of development, accurately determining its forms and stages.
Keywords: Hip Dysplasia; Ultrasound; Children In Infancy